Aqueous Extract of Psiloxylon mauritianum, Rich in Gallic Acid, Prevents Obesity and Associated Deleterious Effects in Zebrafish - Batoul Ghaddar; Laura Gence; Bryan Veeren; Matthieu Bringart; Jean-Loup Bascands; Olivier Meilhac; Nicolas Diotel (MDPI AG, 2022)
Obesity has reached epidemic proportions, and its prevalence tripled worldwide between 1975 and 2016, especially in Reunion Island, a French overseas region. Psiloxylon mauritianum, an endemic medicinal plant from Reunion Island registered in the French pharmacopeia, has recently gained interest in combating metabolic disorders because of its traditional lipid-lowering and "anti-diabetic" use. However, scientific data are lacking regarding its toxicity and its real benefits on metabolic diseases. In this study, we aim to determine the toxicity of an aqueous extract of P. mauritianum on zebrafish eleutheroembryos following the OECD toxicity assay (Organization for Economic Cooperation and Development, guidelines 36). After defining a non-toxic dose, we determined by liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS) that this extract is rich in gallic acid but contains also caffeoylquinic acid, kaempferol and quercetin, as well as their respective derivatives. We also showed that the non-toxic dose exhibits lipid-lowering effects in a high-fat-diet zebrafish larvae model. In a next step, we demonstrated its preventive effects on body weight gain, hyperglycemia and liver steatosis in a diet-induced obesity model (DIO) performed in adults. It also limited the deleterious effects of overfeeding on the central nervous system (i.e., cerebral oxidative stress, blood-brain barrier breakdown, neuro-inflammation and blunted neurogenesis). Interestingly, adult DIO fish treated with P. mauritianum display normal feeding behavior but higher feces production. This indicates that the "anti-weight-gain" effect is probably due to the action of P. mauritianum on the intestinal lipid absorption and/or on the microbiota, leading to the increase in feces production. Therefore, in our experimental conditions, the aqueous extract of P. mauritianum exhibited "anti-weight-gain" properties, which prevented the development of obesity and its deleterious effects at the peripheral and central levels. These effects should be further investigated in preclinical models of obese/diabetic mice, as well as the impact of P. mauritianum on the gut microbiota.